2001
DOI: 10.1016/s0022-5347(05)65928-9
|View full text |Cite
|
Sign up to set email alerts
|

Potent Antitumor Effects of Cd154 Transduced Tumor Cells in Experimental Bladder Cancer

Abstract: Our experimental results suggest that the potent antitumor effects of CD154 gene transduction should be considered for immunostimulatory gene therapy for bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…This particular vector was successfully used in animal studies aiming to develop an immunogene therapy for bladder cancer. 15 The present results indicate that adenoviruses are promising tools for transferring genes into human bladder cancer cells.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…This particular vector was successfully used in animal studies aiming to develop an immunogene therapy for bladder cancer. 15 The present results indicate that adenoviruses are promising tools for transferring genes into human bladder cancer cells.…”
Section: Introductionmentioning
confidence: 56%
“…15 As a negative control, the Ad-dl70-3 'empty' control vector was used (a kind gift from Dr Frank Graham, McMaster University, Hamilton, Ontario).…”
Section: Adenoviral Vectorsmentioning
confidence: 99%
“…Whereas CD154 gene therapy was successfully applied in some animal models of solid tumors including bladder cancer, 16,17 the immunological mechanisms of this therapy remain poorly defined. It has been shown that triggering of CD40 on DCs induces expression of costimulatory signals ( CD80, CD86 ) and adhesion molecules (CD54 ) and leads to efficient cross -priming of CTLs.…”
Section: Discussionmentioning
confidence: 99%
“…To further assess the role of cytotoxic lymphocytes we performed cytotoxicity assays with splenocytes from mice vaccinated with MB49 expressing CD154. Based on previous studies, 17 mice were injected four times in weekly intervals with MB49 expressing CD154 to obtain full protection against a subsequent challenge with parental MB49. Splenocytes from vaccinated mice that rejected a challenge with parental tumor and splenocytes from naïve control mice were isolated, and purified CD8 cells were restimulated with irradiated parental MB49.…”
Section: Cd154 -Expressing Tumor Cells Efficiently Activate Autologoumentioning
confidence: 99%
“…For example, we have shown that adenoviruses expressing CD40L in the tumor enhance Th1 immunity with infiltration of T-cells at the same time reducing Tregs and MDSCs and promoting M2 to M1 switch. [54][55][56] In human bladder cancer patients, an adenovirus expressing CD40L induced large T-cell infiltrates in the bladder wall. 57 …”
Section: Conditioning Of Patients Receiving Car T-cell Therapymentioning
confidence: 99%